AUTOMATIC CONTROL SYSTEM FOR REGULATED HIGH TEMPERATURE MAIN COMBUSTION CHAMBER OF MANEUVERABLE AIRCRAFT MULTIMODE GAS TURBINE ENGINE - T. V. Gras’Ko; S. A. Мayatsky (Научный вестник МГТУ ГА)
The paper describes choosing and substantiating the control laws, forming the appearance the automatic control system for regulated high temperature main combustion chamber of maneuverable aircraft multimode gas turbine engine aimed at sustainable and effective functioning of main combustion chamber within a broad operation range.